Confronting critical issues of race and the need for decolonizing education in Canada: Problematizing the implementation of culturally relevant pedagogy, a Nova Scotian story - Mackey, Wendy (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 2025)
The purpose of this article is to confront critical issues of race and add a missing critical analysis of the attempts to implement culturally relevant pedagogy (CRP) within education in Nova Scotia and across North America. This critical analysis addresses the inequitable learning environments facing Black learners. The stories of both pre-service and in-service teachers highlight the need for educators, educational leaders, and policymakers to embed decolonizing steps to implement CRP and overcome systemic racism in education. Their accounts demonstrate that changes in policies have not led to an understanding of CRP, decolonizing, or an interruption to systemic racism. Without decolonizing steps, including giving educators the time and opportunity to decolonize their thinking, efforts to implement CRP will fail.